Developing clinical guidelines and assessing the quality of medical care using the RAND/UCLA method - O. O. Buzuverova; V. K. Fedyaeva; O. A. Sukhorukikh (Фармакоэкономика, 2020)
Introduction. The RAND/UCLA system is commonly used in healthcare economics as it allows one to consider both the relevant scientific data and the opinion of leading experts for deciding on the specifics of medical care.Objective. To analyze the recommendations and practical aspects of the RAND/UCLA and the international experience in using this method; to analyze the feasibility of its application in the Russian Federation, including the basic documents regulating the national medical care.Materials and methods. We analyzed the information available in the RAND corporation website and the PubMed bibliographic database.Results. An analysis of the original information provided by the developers of the RAND/UCLA method showed that using this method involves several stages: selecting a subject to be further studied, reviewing the scientific literature on this subject, choosing the expert commission, and preparing documents for its work; the voting stage is followed by a voting results analysis. The international experience on the applications of the RAND/UCLA method in healthcare demonstrates the successful use of this method in different countries. The use of the RAND/UCLA method in the healthcare system of the Russian Federation can contribute to improving the quality of medical care and the rational use of healthcare resources.Discussion. Currently, the RAND/UCLA method is internationally used to develop clinical guidelines, criteria for assessing the quality of medical care, and feasibility of medical interventions.Concusion. In the Russian Federation, the application of the RAND/UCLA method can prove useful for developing clinical guidelines and related documentation.